2013
DOI: 10.1177/0363546513485358
|View full text |Cite
|
Sign up to set email alerts
|

Lower Injury Rates for Newcomers to Professional Soccer

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…16 Another female youth study did find that more highly skilled players were at increased risk of injury but they did not stratify by position. 19 A number of studies of professional players have stratified risk by position and found that goalies are at lower risk with no difference among the field players, 20,17 with one study finding higher injury risk for forwards and central defenders. 21 Why female youth defenders are at higher risk than other positions is unclear, but it may be that they are less skilled or more willing to tackle and are coached harder to tackle at an early age thus placing themselves at higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…16 Another female youth study did find that more highly skilled players were at increased risk of injury but they did not stratify by position. 19 A number of studies of professional players have stratified risk by position and found that goalies are at lower risk with no difference among the field players, 20,17 with one study finding higher injury risk for forwards and central defenders. 21 Why female youth defenders are at higher risk than other positions is unclear, but it may be that they are less skilled or more willing to tackle and are coached harder to tackle at an early age thus placing themselves at higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…One factor that may contribute to this heterogeneity of results is players’ age. While evidence is somewhat conflicting [ 14 ], some studies have suggested that injury rates in football would be increasing with age [ 13 , 15 ]. In our study, injury IR was slightly higher in the young (IR = 7.6) as compared to the middle (IR = 7.0) and older (IR = 6.8) age group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is of special interest to investigate whether the types and incidence rates of football-related injuries would be influenced by specific risk factors, such as players’ age or playing position. As regards the possible association of age with injury rates, conflicting evidence has been reported in the literature [ 13 15 ]. Further, it is not currently known whether younger and older players would be predominantly affected by certain types of injuries.…”
Section: Introductionmentioning
confidence: 99%
“…They found a close connection between a previous and a current Achilles tendon injury and the risk of a renewed injury was higher after short recovery phases. Kristenson, Waldén, Ekstrand, and Hägglund ( 2013 ) pointed to a lower risk of injuries in newcomers (first year as a professional football player); however, they showed a higher number of stress fractures. Ekstrand and Van Dijk ( 2013 ) reported that fractures in the fifth metatarsal are significantly more frequent in younger players during the preseason with high-intensity training load.…”
Section: Introductionmentioning
confidence: 99%